2015
DOI: 10.1111/1462-2920.12677
|View full text |Cite
|
Sign up to set email alerts
|

The production of nitric oxide by marine ammonia‐oxidizing archaea and inhibition of archaeal ammonia oxidation by a nitric oxide scavenger

Abstract: Nitrification is a critical process for the balance of reduced and oxidized nitrogen pools in nature, linking mineralization to the nitrogen loss processes of denitrification and anammox. Recent studies indicate a significant contribution of ammonia-oxidizing archaea (AOA) to nitrification. However, quantification of the relative contributions of AOA and ammonia-oxidizing bacteria (AOB) to in situ ammonia oxidation remains challenging. We show here the production of nitric oxide (NO) by Nitrosopumilus maritimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
169
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 78 publications
17
169
0
Order By: Relevance
“…NO is produced and immediately consumed during active ammonia oxidation by N. viennensis EN76 T The initial, rapid production of NO followed by its equally rapid consumption during ammonia-dependent O 2 consumption by N. viennensis differed from results in similar experiments with N. maritimus SCM1 (Martens-Habbena et al, 2015). In this prior study, N. maritimus SCM1 produced NO at a steady-state level prior to its consumption once NH 4 + was depleted or its partial consumption at saturating concentrations of NH 4 + .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…NO is produced and immediately consumed during active ammonia oxidation by N. viennensis EN76 T The initial, rapid production of NO followed by its equally rapid consumption during ammonia-dependent O 2 consumption by N. viennensis differed from results in similar experiments with N. maritimus SCM1 (Martens-Habbena et al, 2015). In this prior study, N. maritimus SCM1 produced NO at a steady-state level prior to its consumption once NH 4 + was depleted or its partial consumption at saturating concentrations of NH 4 + .…”
Section: Discussionmentioning
confidence: 80%
“…Martens-Habbena et al (2015) demonstrated that NO accumulated in N. maritimus SCM1 cultures during active oxidation of NH 4 Cl in a closed microrespirometry chamber, and was released at higher levels under saturating versus non-saturating availability of NH 4 Cl. Exposure to increasing concentrations of an NO-scavenging compound over a 24 h period resulted in decreased levels of nitrite production in batch cultures of ammonia-oxidizing Thaumarchaea, but not bacteria (Martens-Habbena et al, 2015). The authors concluded that NO was either released as a free intermediate during ammonia oxidation by N. maritimus, or it could serve a functional role as an electron delivery mechanism to ammonia monooxygenase, an idea that has been proposed previously .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…They are generally recognized as the main drivers of oceanic nitrification (5)(6)(7), are closely coupled with anammox organisms in oxygen minimum zones (OMZs) (8)(9)(10), and have been implicated as a source of the greater part of oceanic emissions of the ozone-depleting greenhouse gas nitrous oxide (11). Their wide habitat range suggests both high ecotypic diversity and adaptive capacity (12,13).…”
mentioning
confidence: 99%